Improvement of biochemical parameters in type 1 diabetic rats after the roots aqueous extract of yacon [Smallanthus sonchifolius (Poepp.& Endl.)] treatment - Oliveira, Gilberto Ornelas [UNESP]; Braga, Camila Pereira; Fernandes, Ana Angelica Henrique [UNESP] (Elsevier, 2013)
The aim of this study was to evaluate the effect of yacon (Smallanthus sonchifolius) (Poepp.& Endl.) on clinical parameters under diabetic conditions. The aqueous extract of yacon tuberous roots (YRAE; 0.76gfructankg-1 body weight) was prepared at the moment of each administration. Thirty-two male rats were divided into four groups (n=8): control group (C); group that received YRAE (Y); untreated diabetic group (DM1); and diabetic group treated with YRAE (Y-DM1). The diabetes mellitus was induced by streptozotocin (60mgkg-1 body weight). The animals from Y2 and Y-DM1 received YRAE by gavage, at 7-day intervals, for 30days. The aqueous extract of yacon roots decreased (p<0.05) the water and food intake in diabetic rats (Y-DM1). YRAE treatment reduced (p<0.05) glycaemia, total cholesterol, VLDL-c, LDL-c and triacylglycerol levels in diabetic rats (YRAE). HDL, urea and creatinine levels did not differ (p>0.05) between the Y and Y-DM1 groups. YRAE normalised alanine aminotransferase (ALT) activity, when comparing DM1 and Y-DM1 rats, but had no effect on lactate dehydrogenase activity (LDH). In conclusion, YRAE was sufficient for controlling water and food consumption, hyperglycaemia and dyslipidaemia, and promote the reduction of the ALT, suggesting a hepatoprotective effect in rats with STZ-induced DM1. © 2013 Elsevier Ltd.
Keywords: Diabetes mellitus; Fructans; Metabolism; Streptozotocin; Yacon; alanine aminotransferase; cholesterol; creatinine; glucose; high density lipoprotein cholesterol; lactate dehydrogenase; plant extract; Smallanthus sonchifolius extract; streptozocin; triacylglycerol; unclassified drug; urea; very low density lipoprotein cholesterol; alanine aminotransferase blood level; animal experiment; body weight; cholesterol blood level; controlled study; creatinine blood level; drug efficacy; dyslipidemia; enzyme activity; fluid intake; food intake; gluconeogenesis; glucose blood level; hyperglycemia; insulin dependent diabetes mellitus; lactate dehydrogenase blood level; liver protection; male; nonhuman; plant root; rat; Smallanthus sonchifolius; streptozocin diabetes; triacylglycerol blood level; urea blood level